Creating healthy workplaces : stress reduction, improved well-being, and organizational effectiveness. - Biron, Caroline; Burke, Ronald J.; Cooper, Cary L. (Farnham : Ashgate Publishing Ltd, 2014)
Creating Healthy Workplaces includes interventions that relate the efforts undertaken by researchers and organizations to reduce stress and improve the mental and physical health of employees through positive change initiatives. Those working in the field of occupational stress have received criticism that too much emphasis has been placed on negative issues and that positive initiatives have been largely ignored. This book delves into both the positive and the stress fields and compares the types of interventions each entail. Some of the interventions described target individuals and their at.
Implementing interventions -- Interventions to prevent mental health problems at work : facilitating and hindering factors / Jauvin N., Bourbonnais R., Vézina M., Brisson C. and Hegg-Deloye, S. -- Implementing an organizational intervention on quality of life at work : key elements and reflections / Caroline Biron, France St-Hilaire and Jean-Pierre Brun -- Merging occupational health, safety and health promotion with lean : an integrated systems approach (the leanhealth project) / Terese Stenfors-Hayes, Henna Hasson, Hanna Augustsson, Helena Hvitfeldt Forsberg, Ulrica von Thiele Schwarz -- Ehealth interventions for organizations -- potential benefits and implementation challenges / Henna Hasson, Ulrica von Thiele Schwarz, Karin Villaume, Dan Hasson -- Concluding remarks / Caroline Biron.
English.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Work environment -- Psychological aspects; Job stress; Industrial safety; Organizational effectiveness; Electronic books